DOI: 10.11606/d.48.2018.tde-08052018-110949
|View full text |Cite
|
Sign up to set email alerts
|

Felicidade e significado: um estudo sobre o bem-estar em profissionais da educação do estado de São Paulo

Abstract: AGRADECIMENTOSEscrever os agradecimentos de um trabalho científico é um ato extremamente gratificante, pois se trata, na verdade, de uma jornada nas lembranças dos inúmeros acontecimentos vividos até o momento. E nessa viagem mental, o maior desafio é identificar todas as pessoas que tiveram participação e exerceram uma generosa contribuição para que o trabalho fosse realizado com dedicação. Diante disso, seguimos para esse prazeroso desafio.Agradeço ao financiamento oferecido pelo CNPq. Pois graças a bolsa de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 61 publications
(89 reference statements)
0
10
0
2
Order By: Relevance
“…A field survey was carried out with 89 students from a private educational institution in the extreme south of Bahia through a closed questionnaire. The main results obtained in the sample were the presence of many symptoms that occurred in the three main dimensions approached by Benevides-Pereira (2002). This research's current theme must be observed accurately by the people management because it is a silent and devastating danger to lives and it represents a warning factor for enterprises around the modern world.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…A field survey was carried out with 89 students from a private educational institution in the extreme south of Bahia through a closed questionnaire. The main results obtained in the sample were the presence of many symptoms that occurred in the three main dimensions approached by Benevides-Pereira (2002). This research's current theme must be observed accurately by the people management because it is a silent and devastating danger to lives and it represents a warning factor for enterprises around the modern world.…”
mentioning
confidence: 84%
“…Benevides Pereira (2002) completes that it is a process that develops sequentially, and its three dimensions must be considered to characterize the syndrome. According to the aforementioned author, the Emotional Exhaustion dimension presents characteristics that influence motivation, and the feeling that you have reached the limit of your attempts, whether social or organizational.…”
Section: Burnout Syndrome (Concept Origin Approaches and Timeliness)mentioning
confidence: 99%
See 2 more Smart Citations
“…Iniciamos com as diversas concepções de felicidade na literatura localizada. Pereira (2017) destaca que os conceitos de felicidade estão sujeitos à concepção pessoal do pesquisado e do pesquisador em relação ao contexto, do lugar de onde se fala. Associamos a este conceito o entendimento de que a felicidade é tambem um sentimento resultante de experiências concretas e subjetivas associadas a uma sensação de bem-estar, de alegria, de paz e gratidão existencial.…”
Section: Introductionunclassified